An inquiry into the determinants of graduate entrepreneurship in Hong Kong and Guangzhou (Mainland China) - Frank Bickenbach; Dirk Dohse; Wan-Hsin Liu (Kiel Institute for the World Economy (IfW), 2014)
Based on original survey data, this paper analyses and compares the role of personal traits and social capital in determining entrepreneurial intentions of students in Hong Kong and in Guangzhou (mainland China). The two cities are culturally closely related but differ strongly with respect to their formal institutions and the maturity of their business environment. Our findings suggest that the determinants of entrepreneurial intentions among students in Hong Kong very much resemble those found in Western economies, whereas the entrepreneurial mindsets of students in Guangzhou differ substantially from previous findings.
Keywords: M13; O15; 330; entrepreneurial intention; self-employment preference; personal traits; social capital; China; Hong Kong